Angiopoietin2 is associated with coagulation activation and tissue factor expression in extracellular vesicles in COVID-19 - Barbosa, Mayck Silva; de Lima, Franciele; Peachazepi Moraes, Carla Roberta; Borba-Junior, Ivanio Teixeira; Huber, Stephany Cares; Santos, Irene; Bombassaro, Bruna; Dertkigil, Sergio San Juan; Ilich, Anton; Key, Nigel S.; Annichino-Bizzacchi, Joyce M.; Orsi, Fernanda Andrade; et al. (Frontiers in Medicine, 2024)
Coagulation activation in immunothrombosis involves various pathways distinct from classical hemostasis, offering potential therapeutic targets to control inflammation-induced hypercoagulability while potentially sparing hemostasis. The Angiopoietin/Tie2 pathway, previously linked to embryonic angiogenesis and sepsis-related endothelial barrier regulation, was recently associated with coagulation activation in sepsis and COVID-19. This study explores the connection between key mediators of the Angiopoietin/Tie2 pathway and coagulation activation. The study included COVID-19 patients with hypoxia and healthy controls. Blood samples were processed to obtain platelet-free plasma, and frozen until analysis. Extracellular vesicles (EVs) in plasma were characterized and quantified using flow cytometry, and their tissue factor (TF) procoagulant activity was measured using a kinetic chromogenic method. Several markers of hemostasis were assessed. Levels of ANGPT1, ANGPT2, and soluble Tie2 correlated with markers of coagulation and platelet activation. EVs from platelets and endothelial cells were increased in COVID-19 patients, and a significant increase in TF + EVs derived from endothelial cells was observed. In addition, ANGPT2 levels were associated with TF expression and activity in EVs. In conclusion, we provide further evidence for the involvement of the Angiopoietin/Tie2 pathway in the coagulopathy of COVID-19 mediated in part by release of EVs as a potential source of TF activity.